Environmental pollutants as risk factors for neurodegenerative disorders: Alzheimer and Parkinson diseases - Chin-Chan, Miguel; Navarro-Yepes, Juliana; Quintanilla-Vega, Betzabet (Frontiers in Cellular Neuroscience, 2015)
Neurodegenerative diseases including Alzheimer (AD) and Parkinson (PD) have attracted attention in last decades due to their high incidence worldwide. The etiology of these diseases is still unclear; however the role of the environment, from diet to the new nanomaterials as putative risk factors has gained importance. More worryingly is the evidence that pre- and post-natal exposures to environmental factors predispose to the onset of neurodegenerative diseases in later life. Neurotoxic metals such as lead, mercury, aluminum, cadmium and arsenic, as well as some pesticides and metal-based nanoparticles have been involved in AD due to their ability to increase beta-amyloid (Aβ) peptide and the phosphorylation of Tau protein (P-Tau), causing senile/amyloid plaques and neurofibrillary tangles characteristic of AD. The exposure to lead, manganese, solvents and some pesticides has been related to hallmarks of PD such as mitochondrial dysfunction, alterations in metal homeostasis and aggregation of proteins such as α-synuclein (α-syn), which is a key constituent of Lewy bodies, a crucial factor in PD pathogenesis. Common mechanisms of environmental pollutants to increase Aβ, P-Tau, α-syn and neuronal death have been reported, including the oxidative stress mainly involved in the increase of Aβ and α-syn, and the reduced activity/protein levels of Aβ degrading enzymes such as neprilysin or insulin degrading enzyme. In addition, epigenetic mechanisms by maternal nutrient supplementation and exposure to heavy metals and pesticides have been proposed to lead phenotypic diversity and susceptibility to neurodegenerative diseases. This review discusses data from epidemiological and experimental studies about the role of environmental factors in the development of idiopathic AD and PD, and their mechanisms of action.